Measuring Impact. Making Use of the Portfolio: Organizational Learning at USAID - and Peabody, Shawn (USAID, 2015)
This technical analysis explores previous and ongoing social learning efforts, best practices, challenges, and lessons in USAID as a foundation for improving the implementation and design of the Agency’s forestry and biodiversity programs. This analysis is particularly relevant as the Bureau of Economic Growth, Education and the Environment’s Office of Forestry and Biodiversity (E3/FAB) begins to develop a Cross-Mission Learning Program under the Measuring Impact initiative, a five-year activity to promote the adoption of best practices in the USAID program cycle among Missions using biodiversity funds. The findings reported in this document can help inform the overall design and structure of the Learning Program and provide insight into possible challenges and best practices.